SISTEM KODE CERPEN INDONESIA POPULER DALAM KUMPULAN CERPEN DAMARCINNA KARYA BUSTAN BASIR MARAS: PENDEKATAN SEMIOTIKA ROLAND BARTHES) (Code System of Indonesian Popular Short Story in Short Story Collection Damarcinna by Bustan Basir Maras: Semiotical Approach of Roland Barthes) - Adri Maddualeng (Balai Bahasa Sulawesi Selatan, 2009)
Semiotics is a sign study and every thing which are related to the sign like sign system and process of sign usage of a sign system, and as a language sign system in literary text is not only related to the first level meaning, but also more on the second level meaning. Code systems include, action code, puzzle code, culture code, connotative code, and simbolic code.